Aktivitas Ekonomi Masyarakat di Sekitar Mesjid Al-Markaz Al-Islami Makassar (Sebuah Tinjauan Kebudayaan Islam) - Syamsuez Salihima (Rihlah : Jurnal Sejarah dan Kebudayaan, 2014)
Community Economic Activity Around Almarkas Masjid Al-Islami Makassar: A Review of Islamic Culture. The central issue in this study is the Mosque of Al - Markaz al - Islami Makassar reveal new phenomena with market tradition that adorn celebration Islamic holy days. In terms of the traditional Islamic culture is a new phenomenon that is interesting to study through this research. The market is a means of buying and selling that bring together buyers and sellers who gave birth to a healthy transactions between them. What happens in the court of Al - Masjid Al - Islami Makassar Headquarters indeed a new tradition certainly be an interesting phenomenon because market participants in general are people who are aware of the function of the mosque. Associated with the Islamic tradition of religiosity based on the elements that promote the concept of Al - Quran and Hadith that turned out to purchase it is a tradition that is set in the legal sources that tentutsaja if executed properly or in accordance with the rules then it will get the glory. Economic activity in the al - al - Islami Headquarters certainly have differences in their purpose element carrying out market or buy goods selling at Masjid Al - Headquarters Al - Islami they make buying and selling while conducting worship, Sellers also easily offer their goods because economic activity is concentrated in one place, namely the courtyard of the mosque, making it easier for consumers looking for all kinds of needs them. The attractiveness of the market on big days in the Al - Al - Islami headquarters in the context of how to dress consumers and sellers in the market on a day -to-day religious identical to the Islamic dress code